Evaluation of a Passive Anion‐Exchange Membrane Micro Fuel Cell Using Glycerol from Several Sources. Issue 1 (19th December 2018) - Olivares‐Ramírez, J. M.; Dector, A.; Bañuelos‐Días, J. A.; Amaya‐Cruz, D. M.; Ortiz‐Verdín, A.; Jiménez‐Sandoval, O.; Sabaté, N.; Esquivel, J. P.
Abstract: This paper addresses energy generated in a passive anion‐exchange membrane micro fuel cell (PAEMμFC) using glycerol from several kinds of sources: high‐purity glycerol (HPG), saponification process‐derived glycerol (SPDG), crude glycerol from sunflower oil biodiesel (CGSOB) and crude glycerol from cooking oil biodiesel (CGCOB). Spectrophotometry, volumetric Karl Fischer, gas chromatography, calorimetry, Fourier transform infrared, and cyclic voltammetry were employed for the glycerol samples characterization. The PAEMμFC was tested using 0.1M glycerol of each type, achieving power densities of 1.008, 0.932, 0.871, and 0.865 mW cm −2 for HPG, SPDG, CGSOB and CGCOB, respectively. On the other hand, commercially available software from ANSYS, Inc. was used to determine the fuel velocity and pressure in the fuel reservoir and current collector as a complementary evaluation of the PAEMμFC. The results obtained for the prices of the energy of each glycerol sample were presented in order to demonstrate that the cost of energy generated through HPG is approximately 16.5 times the SPDG energy cost and 130 times the CGCOB energy cost.